Assessment of the degree of awareness among post-graduate medical physicians and Pharmacists about look-alike, sound-alike drug and potential medication errors - Munshi, Renuka P.; Tople, Ganesh D.; Munot, Sonali R. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: With thousands of drugs currently in the market, the potential for medication errors due to confusing drug names amongst practising physicians, pharmacists and patients is significant. The existence of confusing drug names is one of the most common causes of medication error. There are many look-alikes, sound-alike (LASA) combinations that could potentially result in medication errors. There is insufficient data about medication errors due to LASA. Hence, we conducted the present study to determine the degree of awareness regarding LASA drugs among post graduate medical physicians and Pharmacists. Methods: This study was a cross-sectional, questionnaire-based survey, conducted among 137 year post graduate medical residents of a tertiary care teaching hospital and 121 local pharmacists in an urban metropolitan Indian city. Results: There were 34% resident doctors and 17% pharmacists were aware of concept of LASA drugs. Only 46% resident doctors and 22% pharmacists had knowledge about the full form of LASA. Among resident doctors, 39% came across prescription errors due to LASA drugs. Only 69% of the pharmacists agreed that they consulted their doctors when they faced problems due to prescription errors due to similar looking and similar sounding drugs. Conclusions: Look-Alike, Sound-Alike (LASA) drugs are common source of medication errors. Our study suggests that there is lack of awareness about LASA drugs amongst resident doctors and pharmacists, which may contribute to occurrence of medication errors. Therefore, combined efforts by prescribers, pharmacists, organizations, manufacturers and patients is required to overcome medication errors due to LASA drugs.